2011
DOI: 10.1002/pssc.201084141
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption and photoluminescence of lumonophore nanocomposites

Abstract: The europium complex tris(dibenzoylmethane)(monophenanthroline)europium (III) (Eu(DBM)3Phen) was successfully incorporated with different molar ratios into organic copolymer matrix of styrene:butylmethacrilate (1:1) (SBMA) via sol–gel process. Spin‐coated thin films were obtained. The layers turn out to be transparent in optical range of investigation. Absorption and luminescence properties of a europium complex on each step of technology nanocomposites of the pure Eu(DBM)3Phen complex powder, its solution wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…A variety of polymers containing rare earth metal have been synthesized (5-7) and applied as functional materials in many fields including (8)(9)(10)(11)(12)(13) sensors and detectors (14)(15)(16)(17)(18), carriers (19,20), and so on (21)(22)(23). Probably, the simplest approach for the preparation of rare earth metal containing polymer is doping or blending (24), which specifically includes sol-gel (25), electrospinning (26), and supercritical carbon dioxide method (27). However, due to the lack of strong binding forces between polymers and rare earth elements, phase separation is highly likely to take place in this doped-type polymer over time, which leads to destabilization.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of polymers containing rare earth metal have been synthesized (5-7) and applied as functional materials in many fields including (8)(9)(10)(11)(12)(13) sensors and detectors (14)(15)(16)(17)(18), carriers (19,20), and so on (21)(22)(23). Probably, the simplest approach for the preparation of rare earth metal containing polymer is doping or blending (24), which specifically includes sol-gel (25), electrospinning (26), and supercritical carbon dioxide method (27). However, due to the lack of strong binding forces between polymers and rare earth elements, phase separation is highly likely to take place in this doped-type polymer over time, which leads to destabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Because of longterm stability, high image resolution, thermal stability, good heat resistance, and superior adhesion to the substrate, film type phosphors are more applicable than powder form [1]. Film phosphor technology can be used in many applications, such as: photoluminescent LCDs, field emission displays, cathode ray tubes, plasma display panels, electroluminescent displays, wavelength converter in solar cell, and other optoelectronic devices [1][2][3] Phosphor film can be synthesized by using several methods such as: sputtering deposition [4], pulsed layer deposition [5], atomic layer deposition [6], spray pyrolysis [7], and chemical vapor deposition [8]. However, these methods require complicated and expensive equipment since need a vacuum condition.…”
Section: Introductionmentioning
confidence: 99%
“…EXPERIMENT BCNO phosphor powder was prepared using simple heating method. Boric acid [B(OH) 3 with Mw = 61.83 g mol í1 ], urea [(NH 2 ) 2 CO, with Mw=60.07 g mol -1 ] and Polyethylene glycol (PEG) [C 2n+2 H 4n+2 O n+2 with Mw=20.000k g mol -1 ] were used as boron, nitrogen, and carbon source, respectively. To obtain homogenous BCNO particles, silica nanoparticles were added.…”
Section: Introductionmentioning
confidence: 99%
“…When carboxylate groups are present in the polymer chain, PVP is able to form complexes with metal ions and inorganic salts. It has been demonstrated that the introduction of the Eu(tta)2(Ph3PO)2NO3 (tta = thenoyltrifluoroacetonate) complex into PVP results in a twofold increase in luminescence intensity [35], which is likely due to the efficient energy transfer to the luminescent metal center through the polymer matrix. It has been demonstrated that complexes of other lanthanides can bind to carboxyl groups of the polymer to form labile metal-polymer complexes (MPC), which results in alterations to the luminescent properties [36].…”
mentioning
confidence: 99%